Motivation among Learners of English in the Secondary Schools in the Eastern Coast of the UAE - Qashoa, Sulaiman Hasan H. (2006)
Everybody needs to have motivation and a reason for action. Second and foreign language learners should be offered the opportunity to be motivated and fulfill their learning orientations. The purpose of this study is to examine the students' integrative and instrumental motivation for learning English in the UAE state secondary schools. Additionally, the study aims to recognize the factors affecting the students' motivation. 0ne hundred students participated in completing a questionnaire reflecting their orientations for learning English and what affects negatively their English learning motivation. Follow up interviews with 20 students, 10 Arab English teachers as well as 3 supervisors were conducted to deepen understanding and interpretation of the results. As expected, the data revealed that the UAE students have a higher degree of instrumentality than integrativeness. Contrary to the findings of other related studies, difficulties with the subject (English) aspects such as vocabulary, structures and spelling were found to be in the first place in terms of demotivating factors. Based on the findings, recommendations and some implications which are of significance to educators and policymakers as well as to researchers are provided. At last, it is hoped that the results of this study could be of much benefit for developing teaching and learning English in the UAE schools.